Application of modern design cultural in Chinese traditional handicraft products for new appearance and commercial value - Alli, Hassan; Md Ishak, Siti Mastura; Wang, Yanyan (Human Resource Management Academic Research Society, 2024)
Chinese traditional handicraft product is unique cultural connotations and exquisite craftsmanship and high global reputation. However, how to combine this unique art form with the modern appearance and enhance its commercial value is an urgent problem. The study aims to explore how the commercial value of traditional Chinese handicraft products can be optimised under the application of modern design culture. Comprehensive literature review is used as main data source to overview and support the issue under investigation. While two (2) case study of Chines traditional handicraft products selected to verify the significance of handicraft products. The results found several factors that needs to be considered during the development of Chinese traditional handicrafts products for better appearance. In addition, incorporating the craftsmanship into cultural and modern creative product elements is recommended that can promotes the seamless integration of handicraft and cultural resources with creative design toward sustainability of inheritance of the Chinese civilization.